Is the Right Research Being Conducted to Advance Knowledge about Breast Reconstruction? An Analysis of the Research Pipeline. Issue 3 (March 2018) - Checketts, Jake X.; Gordon, Joshua; Crawford, Julia H.; Adams, Haley; Duckett, Laurie; Vassar, Matt
Abstract : Background: It has been estimated that up to 85 percent of research is of limited value or wasted, in part because of the wrong research questions being addressed. In this study, the authors identified research gaps for breast reconstruction using guideline recommendations based on low-quality or no evidence. The authors then evaluated whether research was currently being conducted to fill these gaps. Methods: The authors extracted grade C and D options, which are based on limited evidence, from the American Society of Plastic Surgeon's clinical practice guideline for breast reconstruction. For each option, the authors created Participants, Intervention, Comparator, Outcome questions and search strings using a systematic process. Searches were conducted of ClinicalTrials.gov and the World Health Organization's International Clinical Trials Registry Platform to locate new and ongoing studies. The authors also catalogued studies on breast reconstruction funded by the Plastic Surgery Foundation. Results: Of the 10 research gaps, only six were being addressed by new and ongoing research. Timing of reconstruction (immediate or delayed) and use of acellular dermal matrix were most frequently studied. Preoperative referral of a plastic surgeon before mastectomy, complications associated with preoperative breast size, effects of hormone therapy on postoperative outcomes, and methods for detecting local recurrence after mastectomy were not being addressed by new research. Studies funded by the Plastic Surgery Foundation showed a similar pattern. Conclusions: Of the areas identified, some have received more attention than others. Gaps remain. The authors' results should spark interest in conducting research on these topics and, by so doing, strengthen the clinical practice guideline recommendations.